Religious Court Decision Number 222/Pdt.P/2017/PA.Sda: a Judge Considerations on Early Marriage Dispensation in Sidoarjo, Indonesia - Hadius Akbar; Farikh Marzuqi (Universitas Muhammadiyah Sidoarjo, 2019)
Getting married is part of the worship which is sanctified by the Prophet Muhammad, but in Indonesia it has rules if there is someone who is underage married as stated in the law that if someone wants to do a marriage for the prospective bridegroom must be 19 years old and calom the bride must be 16, and can continue the marriage by requesting marriage dispensation permission to the Religious Court. This study aims to determine the judge's consideration of the early marriage dispensation based on the analysis of the Sidoarjo Religious Court Decision Number: 222 / Pdt.P / 2017 / Pa. . The research method used is a juridical-normative research method where data sources are obtained from secondary data and primary data. The results showed that the judgment of judges regarding the dispensation of early marriage was seen from a situation if it was not hastened to marry, something would happen that violated the law because the prospective bride had been pregnant for 1 month, even though the candidate had not reached 16 years but was seen from the evidence and witnesses that they were able to get married.